2006
DOI: 10.1007/s00737-006-0122-3
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre prospective study of perinatal depression in Japan: incidence and correlates of antenatal and postnatal depression

Abstract: A multicentre study on the epidemiology of perinatal depression was conducted among Japanese women expecting the first baby (N = 290). The incidence rate of the onset of the DSM-III-R Major Depressive Episode during pregnancy (antenatal depression) and within 3 months after delivery (postnatal depression) were 5.6% and 5.0%, respectively. Women with antenatal depression were characterised by young age and negative attitude towards the current pregnancy, whereas women with postnatal depression were characterise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
112
2
13

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(142 citation statements)
references
References 52 publications
10
112
2
13
Order By: Relevance
“…Two prospective studies indicated that 1.7% to 4.0% of mothers had new-onset of OCD after childbirth (45,51). When childbearing female patients with OCD attending a clinical setting were retrospectively assessed, the postpartum period was associated with an onset of OCD up to 50% (46)(47)(48)(49)53).…”
Section: Incidencementioning
confidence: 99%
“…Two prospective studies indicated that 1.7% to 4.0% of mothers had new-onset of OCD after childbirth (45,51). When childbearing female patients with OCD attending a clinical setting were retrospectively assessed, the postpartum period was associated with an onset of OCD up to 50% (46)(47)(48)(49)53).…”
Section: Incidencementioning
confidence: 99%
“…These home visits were primarily geared towards groups prone to child abuse, i.e., women with unwanted pregnancies, pregnant adolescents and low-income families [5][6][7]. On the other hand, several studies have been made on the association between unwanted pregnancies and perinatal depression [8][9][10]. In Japan, a home visiting program, Boshi-AiikuKai, has been sponsored by the Mother-Child Nursing Association since the 1930s.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, prevalence rates of depression during pregnancy were significantly higher in low-income countries. The main risk factors associated with these differences are past history of psychiatric disorders, poor antenatal care, poor nutrition, stressful life events, economic deprivation and gender based violence, which are more prevalent in developing countries 4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29 .…”
Section: Introductionmentioning
confidence: 99%